Analysis of Student Responses to E-learning Resources and Activities - Widowati pusporini (Universitas Sarjanawiyata Tamansiswa, 2020)
In early 2020, the outbreak spread in the world. In response to this emergency condition, the world's higher education institutions have been forced to resort to e-learning and digital tools. This study was conducted to find out the students’ responses to resources and activity e-learning. The sample was composed of 37 students. The data were collected by questionnaire and analyzed by mean score and Likert scale. Using ideal normal standards for the various data above, it can be concluded that the student response to e-learning used at the University of Sarjanawiyata Tamansiswa can be described as follows for the student response indicator to the resources in e-learning, has 4.1 mean scores, it can be concluded that students assess resources in e-learning are considered good. Then, the activities in e-learning have a mean score of 3.8. This indicates that it is in a fair category.